2022
DOI: 10.1186/s12891-022-05188-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes one year after a digital musculoskeletal (MSK) program: an observational, longitudinal study with nonparticipant comparison group

Abstract: Background The evidence base for the impact of digital health on musculoskeletal (MSK) outcomes is growing, but it is unclear how much digital MSK programs address pain and function in the intermediate and long term. Methods This observational study of digital MSK program participants versus nonparticipants (n = 2570) examined pain, function, depression, and anxiety at 3, 6, and 12 months, and health care use at 12 months. The intervention group en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 50 publications
4
7
0
Order By: Relevance
“…The observed improvements in mental health scores were higher than those previously reported by other multimodal telerehabilitation interventions [69,70], and were in line with those previously reported by us [37,39] and others [27,32,34,71]. Similar to the present study, Wang et al [71] reported a significant decrease in anxiety symptoms, allowing the transition to a lower level of anxiety according to established thresholds after a telerehabilitation program combining exercise with coaching.…”
Section: Comparison To Prior Worksupporting
confidence: 92%
“…The observed improvements in mental health scores were higher than those previously reported by other multimodal telerehabilitation interventions [69,70], and were in line with those previously reported by us [37,39] and others [27,32,34,71]. Similar to the present study, Wang et al [71] reported a significant decrease in anxiety symptoms, allowing the transition to a lower level of anxiety according to established thresholds after a telerehabilitation program combining exercise with coaching.…”
Section: Comparison To Prior Worksupporting
confidence: 92%
“…In the present study, pain levels reported by both groups at baseline (4.6–4.8 points) were within the range of those described in the literature for CMP both in telerehabilitation (5.8–4.5 points) [ 31 , 32 , 33 , 34 , 52 , 53 , 89 ] and in conventional physical therapy (4.6–5.8 points) studies [ 90 , 91 , 92 ]. When analyzing the impact of telerehabilitation interventions on pain reduction at 1-year, the results varied, possibly depending on a number of factors, including baseline pain severity, type of pain management strategy, length of the intervention and particularly the affected joint (e.g., several anatomic regions (50.9%) [ 31 ], low back (44.8%) [ 93 ], knee (43.9%) [ 32 ], hip (34.5%) [ 32 ], or hip and knee (17.2%) [ 94 ]). In the present study, a 2.43-points change was observed, with the comparison group reporting significantly lower improvement.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, digital interventions allow easy delivery of multimodal approaches, highly recommended for CMP [ 6 , 29 ]. Telerehabilitation for CMP has shown comparable results to in-person physical therapy [ 30 , 31 , 32 , 33 , 34 , 35 ], while reducing costs [ 36 , 37 , 38 ]. Patient participation [ 39 ] and adherence [ 40 ] may also be maximized through these approaches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Some participants registered for the program, created their account, but did not take part in the intervention (i.e., did not completed any game). These individuals were considered "nonparticipants" and were used as a control group (as proposed in previous research 14 ). Similarly, the baseline period of these nonparticipants corresponds to the days prior to the date they were supposed to start the intervention period.…”
Section: Study Design and Participantsmentioning
confidence: 99%